2021
DOI: 10.1111/vox.13044
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐A and SARS‐CoV‐2: an intriguing association

Abstract: Background Blood groups and anti‐A isohemagglutinin may be involved in susceptibility to SARS‐CoV‐2 infection. Materials and Methods We retrospectively studied 268 COVID‐19 convalescent plasma donors and 162 COVID‐19 inpatients (total 430 subjects, confirmed by RT‐PCR) and 2,212 healthy volunteer first‐time blood donors as a control group. These were further divided into two groups: those with anti‐A (blood types O and B) and those without it (types A and AB). Titres of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Our results do not confirm the previous reports that the ABO blood group type affects the anti‐SARS‐CoV‐2 antibody concentration in COVID‐19 convalescents 19–22 . In our cohort, we found no statistically significant differences between the SARS‐CoV‐2 antibody levels in different ABO‐types regardless of which serological method was used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results do not confirm the previous reports that the ABO blood group type affects the anti‐SARS‐CoV‐2 antibody concentration in COVID‐19 convalescents 19–22 . In our cohort, we found no statistically significant differences between the SARS‐CoV‐2 antibody levels in different ABO‐types regardless of which serological method was used.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, it was logical that the following research would focus on the impact of ABO blood group type on the quantity of anti‐SARS‐CoV‐2 antibodies produced in convalescents since the CCP represents a valuable resource for prevention and therapy. Since the resulting studies led to conflicting results, 16–22 we analyzed a larger cohort of 3187 COVID‐19 convalescent plasma donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Madariaga et al reported lower anti‐receptor binding domain (RBD) and anti‐spike antibodies in blood group O CCP donors compared to blood group AB donors 11 . Additionally, de Freitas Dutra et al describe lower titers of neutralizing antibodies and lower levels of anti‐nucleocapsid antibodies in blood groups O and B COVID‐19 individuals compared to blood groups A and AB COVID‐19 individuals 12 . However, additional studies found no correlation between ABO blood type and anti‐nucleocapsid level, anti‐spike‐RBD level, 13 or maintenance of neutralizing antibody titer, 14 in convalescent individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A possible association between SARS-CoV-2-specific antibodies and ABO blood types was previously investigated. It was found that patients with blood types O and B had lower SARS-CoV-2 antibody titres than patients with blood types A and AB [ 26 , 27 ]. A dataset of the ABO blood type distribution in COVID-19 patients published by Zhao et al [ 28 ] was re-analysed by Gerard et al from the perspective of ABO antibodies instead of ABO blood group antigens [ 29 ].…”
Section: Introductionmentioning
confidence: 99%